Comparison of moderate and advanced glaucoma patients in Ghana - Deng L (Dove Medical Press, 2012)
Andrew W Francis1, Michael E Gyasi2, Li Deng3, Haiyan Gong11Boston University School of Medicine, Boston, MA, USA; 2Emmanuel Eye Centre, Accra, Ghana; 3The New England College of Optometry, Boston, MA, USAPurpose: To compare moderate and advanced glaucoma patients in Ghana.Methods: A retrospective cross-sectional study of 164 patients with primary open-angle glaucoma (POAG) were separated into moderate and advanced glaucoma groups. Definitions of moderate and advanced POAG were derived from International Geographical and Epidemiologic Ophthalmology criteria and included clinical assessment of optic disc atrophy and Humphrey automated perimetry. Data were collected at the patient's first visit prior to initiation of therapy. Eligible POAG patients included those ≥30 years old with reliable Humphrey visual field (HVF) results, no past POAG diagnosis, treatment, or evidence of a secondary cause for glaucoma. Main outcome measures included comparisons of intraocular pressure (IOP), cup-to-disk ratio (CDR), best corrected visual acuity (VA), age, Humphrey mean deviation (MD), and pattern standard deviation (PSD).Results: Of 164 charts reviewed, 90 (54.9%) advanced and 74 (45.1%) moderate POAG patients were compared. Mean age was 59.36 versus 55.53 years, respectively. Significant differences in IOP, CDR, CDR asymmetry, and HVF results were described. IOP > 30 mmHg was associated with CDR >0.7 and MD greater than -12 dB in both eyes.Conclusion: Significant differences were found between IOP, CDR, MD and PSD values. HVF is predictive of pretreated IOP, CDR, and severity of POAG and it is strongly encouraged as part of the standard glaucoma work up in all Ghanaian patients.Keywords: glaucoma, intraocular pressure, Ghana